PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERORIENTASI MODEL PEMBELAJARAN PROBLEM BASED LEARNING (PBL) UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS PADA MATERI SISTEM EKSKRESI KELAS VIII SMP - Rizki Indah Anggraini; Evi Suryawati (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The Biological subject in class VIII has a fairly high level of difficulty and is closely related to everyday life. One of the class VIII are quite difficult to grasp and is closely related to life is the material excretion system. The characteristics of the material in this excretion system places emphasis on contextual learning process because of the demand to link between the subject matter with real events in everyday life including health. The purpose of this study is to increase understanding and knowledge of the learners about the excretion system material. This research was carried out in the laboratory of Biology Education Department PMIPA FKIP University of Riau and junior high school 23 Pekanbaru in April-August 2016. This type of research is research development using model ADDIE conducted up to the stage of development. There are 3 is LKS as developed. Data collection instruments in the research is the assessment sheets/validation is LKS, and the now the response of learners. Once LKS as developed, validated by 4 people validator then conducted tests I on 20 students 4 semesters of Biology education and pedagogy, and UR free trial II on 20 learners Class VIII.g. The validation results showed a mean score of 3 contents eligibility aspect is LKS as developed is very valid category, 4.22 average score aspects of design are valid categories, 3.97 and average score is 3.98 pedagogic aspect of the category is valid. The average score of the overall aspect of the third category is LKS is 4.06. The results of the tests showed I score average 4.33 by category. The results of the tests showed a mean score of 4.12 II with a category either. The results of the analysis of the answers on a test I shows the average value of 86 with categories either. LKS Oriented Problem Based Learning (PBL) model on the material excretion system can increase understanding and knowledge about the material and the excretion system can enhance critical thinking skills class VIII junior high school.Key Words: Development, LKS, Problem Based Learning (PBL), Critical thinking, Excretion system.